Implementasi Kurikulum Merdeka pada Pembelajaran Paket C di SKB Kota Semarang: Perspektif Tutor dan Peserta Didik - Nirmala Nirmala; Abdul Arif (Universitas Cokroaminoto Palopo, 2026)
Senior Secondary Equivalent Program is a non-formal educational service equivalent to senior high school, organized by the Community Learning Center (SKB) for learners unable to complete formal education. This study aims to describe the implementation of Merdeka Curriculum-based learning strategies in Package C at SKB Kota Semarang from the perspectives of tutors and learners. A descriptive qualitative approach with a phenomenological perspective was applied, collecting data through semi-structured interviews, observation, and document analysis involving three tutors and three learners. Data validity was ensured through source triangulation and analyzed using the interactive model of Miles, Huberman, and Saldana. Results indicate that tutors formulate learning objectives based on Learning Outcomes through Teaching Objectives and Learning Objective Flow. Project-Based Learning dominates instructional strategies and effectively increases learner enthusiasm. Learning resources are multimodal and contextualized to real-life experiences. Key challenges include limited digital infrastructure, irregular attendance, and absence of standardized program monitoring instruments. This study contributes empirical insights into Merdeka Curriculum implementation in non-formal education, limited to a single educational unit.